Effect of Large Yellow Croaker By-Products on Physical Properties and Thermal Gelling Properties Changes in Reconstituted Surimi Gel - Fen Zhou; Fengchao Wu; Xiaoqing Ren; Jiaxin Guo; Xichang Wang (Foods)
To investigate the effects of water-soluble taste substances (WSTSs) on the physical properties and thermal coagulation properties of reconstituted surimi gels, this study used large yellow croaker muscle (FM) and the WSTS from by-product minced meat (MM) (skin, tail, and head meat (HM)). It was observed that these exogenous additions could effectively improve the surimi gel’s whiteness, gel strength and umami amino acid content. When these were added, the relaxation times of bound water in FM, MM and HM groups were shorter in the 10% exogenous addition treatment, and the surimi particle size (D10, D50, D90, d4, 3, d2, 3) was smaller. This implies a correlation between the WSTS and the moisture preservation capacity of recombinant surimi gels, whereby WSTS facilitates the cross-linking of protein molecules, leading to the formation of a densely interconnected network architecture. This research can provide theoretical guidance for the processing of surimi gel combined fish flavor substances and freshwater surimi, thereby improving the flavor characteristics of freshwater surimi gel.